(untitled) (Legal journal - Research in Legal and Social Sciences, 2021)
The futures and the forwards are financial instruments, very little exploited in Paraguayan economic activities. The reason for their low use in national market might be, to a certain extent, the lack of knowledge of these financing tools. In that sense, this paper covers the following questions: what are the futures and the forwards? What are they for? What is the difference between them two? Do they have legal effect? The exchange market’s development in Paraguay has been very slow and is currently little advanced. Nevertheless, to put it colloquially, everything must be done. However, the Chicago stock exchange, CME onwards, in the United States, started to quote the water in the future market, and as Olav Dirkmaat inquires, ¿is that a blessing or a curse? The excessive commodification of the things is a phenomenon that undeniably affects the whole world, more rapidly in the decades after the year 2000, with the height of the internet, the massive globalization and the dominance of Big Tech. The purpose of this paper is to cover future and forward contracts. The importance of them is preponderant in the development of international trading of commodities, considering that Paraguay stands out for its agro-business.